What Bonds Hold? An Examination of Statewide Bond Referenda in Maine and Other States - Melcher, James (Maine Policy Review, 2016)
Since 1990, Maine has held votes on statewide bond referenda than any other state. In this article, James Melcher tackles three main questions: (1) How often do voters approve bond proposals in Maine, and how does this compare to other states? (2) Are some types of bond referenda more likely to pass than others? (3) Does a bond’s placement on the ballot make it more, or less, likely to pass?
Keywords: bond referenda; Maine; elections